PENGARUH JENIS PUPUK ORGANIK DAN JARAK TANAM TERHADAP PERTUMBUHAN LIDAH BUAYA - Jumini Jumini (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2006)
The Effect of Organic Fertilizer and Planting Space on the Growth of Aloe Jumini dan Syammiah Program Studi Agronomi Fakultas Pertanian Unsyiah ABSTRACT The objectives of this research were to know the effect of organic fertilizer species and planting space, and interaction between them on the growth of aloe. Research was done from February to May 2006 at experiment station of Agriculture Faculty of Syiah Kuala University. Units of treatments were arranged by factorial randomized complete block design with 3 replications. Data collected were analyzed by analysis of variance and followed with honestly significant different test at the level of 5%. The results showed that cow manure was the best for the growth of aloe compared to compos, and the spacing of 70x70 cm was the best planting space. However, the interaction between the two factors showed that widening planting space from 60x60 cm to 70x70 cm with cow manure did not give significant effect; while this gave significant positive effect when using compos.